Movement disorder in GNAO1 encephalopathy associated with gain-of-function mutations. (22nd August 2017) - Feng, Huijie; Sjögren, Benita; Karaj, Behirda; Shaw, Vincent; Gezer, Aysegul; Neubig, Richard R.
Abstract : Objective: To define molecular mechanisms underlying the clinical spectrum of epilepsy and movement disorder in individuals with de novo mutations in the GNAO1 gene. Methods: We identified all GNAO1 mutations reported in individuals with epilepsy (early infantile epileptiform encephalopathy 17) or movement disorders through April 2016; 15 de novo mutant alleles from 25 individuals were introduced into the Gαo subunit by site-directed mutagenesis in a mammalian expression plasmid. We assessed protein expression and function in vitro in HEK-293T cells by Western blot and determined functional Gαo -dependent cyclic adenosine monophosphate (cAMP) inhibition with a coexpressed α2A adrenergic receptor. Results: Of the 15 clinical GNAO1 mutations studied, 9 show reduced expression and loss of function (LOF; <90% maximal inhibition). Six other mutations show variable levels of expression but exhibit normal or even gain-of-function (GOF) behavior, as demonstrated by significantly lower EC50 values for α2A adrenergic receptor–mediated inhibition of cAMP. The GNAO1 LOF mutations are associated with epileptic encephalopathy while GOF mutants (such as G42R, G203R, and E246K) or normally functioning mutants (R209) were found in patients with movement disorders with or without seizures. Conclusions: Both LOF and GOF mutations in Gαo (encoded by GNAO1 ) are associated with neurologic pathophysiology. There appears to be a strong predictive correlation between the in vitro biochemical phenotype and the clinical pattern of epilepsy vs movement disorder.